Features of the American foreign direct investment: the role of the American holdings - Yulia A. Konovalova (RUDN Journal of Economics, 2021)
Article is dedicated to the determination of key features of the United States participation in the international capital movement on the example of FDI outflows and inflows, and confirmation of its heterogeneous nature. Tax reform that has been implemented in the end of 2017 led to the result when USA was deleted of the list of TOP-20 world investors of 2018 (by UNCTAD). The scientific opinion and fears were connected with the forecasts that the tax reform could change the movement of FDI flows back to the USA from foreign countries, especially, and the countries with the low taxes and the most favorable investment regimes. At the same time, it needs to underline that the analysis of U.S. FDI inflows and outflows showed that the negative indicator of U.S. FDI outflow (export) in 2018-2019 was connected with the repatriation of U.S. holding companies profits, that were doing business in countries with the most favorable tax and investment regimes. The authors tried to investigate the nature of the American holdings role and the integration of U.S. in to the global system of FDI and capital movement.